2015
DOI: 10.3183/npprj-2015-30-03-p385-392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of kaolin addition on the dynamics of oxygen mass transport in polyvinyl alcohol dispersion coatings

Abstract: SUMMARY:The permeability of dispersion barriers produced from polyvinyl alcohol (PVOH) and kaolin clay blends coated onto polymeric supports has been studied by employing two different measurement methods: the oxygen transmission rate (OTR) and the ambient oxygen ingress rate (AOIR). Coatings with different thicknesses and kaolin contents were studied. Structural information of the dispersion-barrier coatings was obtained by Fourier transform infrared spectroscopy (FTIR) spectroscopy and scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Aqueous suspensions, based on PVOH and water solutions of kaolin, were prepared and coated onto the PET films according to the procedure described below. 54 The dispersion was drawn down on the PET sheets with a bench rod coater (K202 Control Coater, RK Print Coat Instruments Ltd., Royston, UK) and subsequently dried at 95°C in a heating chamber until the barrier coatings contained only 5% water. The barrier coating reached temperatures of approximately 70°C during drying, as measured by an IR temperature sensor (Thermopoint TPT 62, FLIR system AB, Danderyd, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous suspensions, based on PVOH and water solutions of kaolin, were prepared and coated onto the PET films according to the procedure described below. 54 The dispersion was drawn down on the PET sheets with a bench rod coater (K202 Control Coater, RK Print Coat Instruments Ltd., Royston, UK) and subsequently dried at 95°C in a heating chamber until the barrier coatings contained only 5% water. The barrier coating reached temperatures of approximately 70°C during drying, as measured by an IR temperature sensor (Thermopoint TPT 62, FLIR system AB, Danderyd, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…The FTIR spectra were collected with a Thermo Nicolet FTIR iS10 spectrometer (Madison, USA) in an attenuated total reflectance (ATR) mode using a diamond crystal, which gave a 0.3-lm penetration depth at 3600 cm À1 (see Nyflö tt et al 54 for further details). The orientation of the clay was determined from the FTIR spectra.…”
Section: Fourier Transform Ir Spectroscopymentioning
confidence: 99%
“…Conversely, a second kaolin (Imerys, Cornwall, UK) was claimed to have a width‐to‐thickness ratio of 34 for the totally exfoliated filler (corresponding to the adopted aspect ratio of 9) and was used after purification, following the procedure previously reported by Järnström et al . The kaolin concentration was limited to 10 wt % because previous studies showed that the concentration of kaolin has the greatest impact up to 10 wt % and because of its industrial relevance.…”
Section: Methodsmentioning
confidence: 99%
“…However, the presented model is endowed with a general validity and can thus be employed to describe the transport of penetrant molecules in several types of polymer/filler composite materials. Existing models describe either the tortuous pathway or the polymeric properties, while the presented model describes both the polymer properties and the tortuosity, since both these parameters affect the penetrant transport …”
Section: Introductionmentioning
confidence: 99%
“…Our main motivation is to develop multiscale mathematical modelling strategies of transport processes that can describe, over several space scales, how internal structural features of the filler and of the local defects affect the effective diffusivity of the material, perceived here as a thin long composite membrane. As concrete applications, we have in mind the transport of O 2 and/or CO 2 molecules through packaging materials [28] (layered composite membranes) as well as the dynamics of human crowds through barrier-like heterogeneous environments (active particles walking inside geometries with obstacles). In both cases, a relevant question concerns the possibility of concentration trapping.…”
Section: Background Motivationmentioning
confidence: 99%